Emotional Intelligence and Spiritual Intelligence on Student Learning Motivation - Yunita Stella; Sri Binar; Ani Teguh Purwanto; Jonathan Octavianus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
The purpose of this study is to examine the influence of emotional intelligence and spiritual intelligence on students' learning motivation. The research method employed in this study is quantitative with multiple linear regression analysis. The research was conducted at Sekolah Tinggi Teologi Injili Indonesia Surabaya, and the findings indicate that emotional intelligence and spiritual intelligence have a significant effect on students' learning motivation, accounting for 61.5% of the variance. Specifically, emotional intelligence has a 70.6% effect on learning motivation, while spiritual intelligence has a 76.9% effect. Research Contribution: This study highlights the importance of emotional intelligence and spiritual intelligence in influencing students' learning motivation at Sekolah Tinggi Teologi Injili Indonesia Surabaya. Therefore, educational institutions, particularly Sekolah Tinggi Teologi Injili Indonesia Surabaya, should focus on organizing student activities that promote the development of emotional and spiritual intelligence. Furthermore, educators should employ innovative teaching methods to enhance students' emotional and spiritual intelligence, ultimately leading to increased learning motivation among students.